Development of a brief screening tool for women's mental health assessment in refugee settings: A psychometric evaluation. Issue 7 (July 2015) - Bell, Sue Anne; Lori, Jody; Redman, Richard; Seng, Julia
Abstract Background and purpose The detection of common mental disorders in humanitarian crisis settings requires a screening tool that is feasible to use as well as sensitive and specific. The Self-Report Questionnaire, developed by the World Health Organization in 1994 to detect presence or absence of common mental health disorders, has frequently been used among conflict-affected and refugee populations. Our goal was to identify a highly predictive and reliable subset of items to serve as a screening tool that can be used in busy, over-crowded, and low-resource primary health care settings to identify women who need mental health attention. Methods We analyzed the responses on a version of the Self-Report Questionnaire expanded to include two suicidality items from 810 displaced women living in refugee camps in Rwanda. Screening items were selected and evaluated for predictive ability using logistic regression in a cross-validation process, sensitivity and specificity using receiver operating characteristic curve analysis, and internal consistency analysis. Results A five-item screening tool resulted. Those items are "Do you feel unhappy?", Do you feel easily nervous, tense, or worried?", "Have you lost interest in things?", "Do you have trouble thinking clearly?" and "Has the thought of ending your life been on your mind?". Conclusion The Self-Report Questionnaire-5 may be an important tool for identifying common mental disorders as well as suicide ideation and behaviors when assessing mental health among women in crisis situations. Further evaluation of this tool is warranted.